A code for the analysis of missions with electrodynamic tethers. (September 2022) - Sánchez-Arriaga, Gonzalo; Borderes-Motta, Gabriel; Chiabó, Luca
Abstract: The main novelties and capabilities of the second version of the Bare Electrodynamic Tether Mission Analysis Software (BETsMA v2.0) are presented. Recent advances on Orbital-Motion-Theory have been incorporated to the electric model of Low-Work-function Tethers (LWTs). An electric model that considers a switch to embed a power supply or a resistor between a Bare Electrodynamic Tether (BET) and an electron emitter is also introduced. For both types of tethers (LWT and BET) and modes of operations (active and passive), robust and efficient numerical algorithms to compute the current and voltage profiles were constructed based on a change of variable proposed in a previous work. The capabilities of the code are illustrated by considering two relevant scenarios. For a BET in the passive mode, it was shown that onboard power can enhance tether performance and reduce significantly the deorbit time. For a BET in the active mode, a performance map varying the orbit inclination, the length of the insulated tether segment, and the power was constructed. For both cases, the code was used to investigate through simulations the conditions to keep constant the electric current at the electron emitter. Highlights: The second version of the tether software BETsMA v2.0 is presented. Electric models for bare and low-W tethers in active and passive modes are given. Tether performances in the active and the passive modes are shown. The impact of a power supply on tether performances in the passive mode is shown.